Bibliometric analysis of the abstracts published in the Proceedings of the Jaffna Science Association (1992-2013) - Manikumar, T.; Chandrasekar, K. (Proceedings of Jaffna Science Association, 2014)
Scholarly publications are often used as a measure of success of research work. Bibliometrics offers a powerful set of methods and measures for studying the structure and process of scholarly communication. This paper describes the bibliometric review of the abstracts published in the proceedings of the JSA during a 22-year period. In this present study, bibliographical details of 741 abstracts available in 20 volumes of the JSA proceedings were collected, tabulated, analyzed and reported. The attributes such as, yearly distribution of abstracts, authorship pattern, contributing institutions, language, subject coverage, and layout of the abstracts were taken into consideration for this bibliometric analysis. Results showed that there is variation in the number of abstracts published per year, ranging from 17 to 74. Besides, 78.27% of the published abstracts were related to pure and applied sciences. Collaborative authorship is a prominent feature observed in 83.80% of the abstracts, which is one of the widely practiced trends in scholarly communication. Among the contributing institutions, over 95% of the abstracts have been contributed by the University of Jaffna independently or jointly with other institutions. In the terms of language attribute, except 2 abstracts (in Tamil) all the 739 abstracts have been published in English. The analysis of subject coverage revealed that agriculture and biochemistry are the key disciplines where 31.98% and 19.84% of the abstracts published, respectively. This indicates the research trend in the region, during the last two decades or so. Furthermore, regarding the layout of the abstracts, it was found that 80.70% of the abstracts comply with the guidelines prescribed by the JSA for format and 43.99% of the abstracts fall in the range of 200-300 word limits. In conclusion, this bibliometric study helped to recognize the research trend of the region, and evaluate the research outputs by employing quantitative methods.
Keywords: Bibliometrics; Scientific production